Determinant Factors Of Hypertension Incidence In The Productive Age Group (15–64 Years) In The Working Area Of WEE Karou Community Health Center, West Sumba Regency - Febyola Giovanni Lumenta Febyola; Sigit Purnawan; Yuliana Radja Riwu; Deviarbi Sakke Tira (CV. AFDIFAL MAJU BERKAH, 2026)
Hypertension is a non-communicable disease characterized by systolic blood pressure ≥140 mmHg and/or diastolic blood pressure ≥90 mmHg, which often occurs without symptoms but can lead to serious complications such as cardiovascular disease, stroke, and chronic kidney disease. Productive-age populations are increasingly at risk due to lifestyle-related factors. This study aimed to analyze the determinant factors of hypertension among productive-age individuals (15–64 years) in the working area of Wee Karou Community Health Center, Sumba Barat Regency. This study employed a quantitative analytic observational design using a case-control approach. The study was conducted in January–February 2026. The sample consisted of 170 respondents, including 85 cases (hypertensive individuals) and 85 controls (non-hypertensive individuals), selected using simple random sampling with matching based on age and gender. Data were collected using questionnaires and medical record documentation. Data were analyzed using univariate and bivariate analysis with the Chi-square test and Odds Ratio (OR) at a 95% confidence level. Results: The results showed that obesity was significantly associated with hypertension (p = 0.044; OR = 1.97), smoking habits were significantly associated with hypertension (p = 0.044; OR = 1.97), poor sleep quality showed a significant association (p = 0.001; OR = 2.91), and betel quid consumption was also significantly associated with hypertension (p = 0.037; OR = 2.23). Among all variables, poor sleep quality showed the strongest association with hypertension incidence. Conclusion: Obesity, smoking habits, poor sleep quality, and betel quid consumption are determinant factors of hypertension among productive-age individuals in the Wee Karou Health Center area.